UTILIZING GLASS POWDER AND LIMESTONE DUST AS AN ALTERNATIVE TO PORTLAND CEMENT FOR STABILIZATION OF CLAYEY SOILS - HASSAN, HUSSEIN JALAL ASWAD (Journal of Duhok University, 2023)
This study investigates the potential of limestone dust and glass powder, byproducts of limestone quarrying and recycled glass waste, respectively, as environmentally-friendly alternatives to cement for soil stabilization. Laboratory tests were carried out on clayey soils mixed with varying dosage rates (3%, 6%, and 9%) of glass powder, limestone dust and Portland cement. The geotechnical properties, including Atterberg limits, compaction and unconfined compressive strength, were evaluated to assess their effectiveness in soil stabilization. The results demonstrate that both glass powder and limestone dust can serve as applicable alternatives to cement, offering sustainable solutions with improved soil stability. This research contributes to reducing the reliance on cement for soil stabilization, promoting environmentally-friendly practices in construction.